2016
DOI: 10.1111/jjns.12107
|View full text |Cite
|
Sign up to set email alerts
|

Effects of relational coordination among colleagues and span of control on work engagement among home‐visiting nurses

Abstract: Agency span of control is a moderating factor on the positive effect of relational coordination with nursing colleagues on staff nurse work engagement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…As indicated in future directions, the other possible outcomes of relational coordination are employee and client/customer related. A limited number of studies focused on these outcomes, for example, HR-related outcomes of relational coordination investigated in previous studies include job satisfaction, motivation, professional efficacy, work engagement and proactive work behavior, job involvement, sense of social support, confidence in collaboration, and psychological safety (Naruse, et al, 2016;Havens, Vasey, Gittell, & Lin, 2010;Carmeli & Gittell, 2009). In present work, we extended the outcomes and included employee creative involvement as an employee-related outcome.…”
Section: Background Of the Studymentioning
confidence: 99%
See 2 more Smart Citations
“…As indicated in future directions, the other possible outcomes of relational coordination are employee and client/customer related. A limited number of studies focused on these outcomes, for example, HR-related outcomes of relational coordination investigated in previous studies include job satisfaction, motivation, professional efficacy, work engagement and proactive work behavior, job involvement, sense of social support, confidence in collaboration, and psychological safety (Naruse, et al, 2016;Havens, Vasey, Gittell, & Lin, 2010;Carmeli & Gittell, 2009). In present work, we extended the outcomes and included employee creative involvement as an employee-related outcome.…”
Section: Background Of the Studymentioning
confidence: 99%
“…Findings of studies which investigated the relationship between relational coordination and some favorable employee-related outcome indicate that relational coordination is associated with proactive work behavior and engagement, professional efficacy, greater career satisfaction, identification with organizational values, and motivation (Naruse, et al, 2016;Cramm, & Nieboer, 2014;Havens, et al, 2010). Other outcomes of relational coordination include psychological safety (Carmeli & Gittell, 2009); job involvement and competence (Albertsen, Wiegman, Limborg, Thornfeldt, & Bjorner, 2014); and perceived justice and employee organizational commitment (Alvarez, 2014;Wright, 2015).…”
Section: Relational Coordination and Employee Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…; Warshawsky, Havens, and Knafl ; Havens, Warshawsky, and Vasey ; Albertsen et al. ; Naruse, Sakai, and Nagata ).…”
mentioning
confidence: 99%
“…Some have described this relational type of coordination as a state of flow in which egos are relinquished in service of a clearly shared purpose, and actions are informed by collective purpose and collective mind, with respect for the contributions offered by each (Quinn and Dutton 2005). Previous studies have found relational coordination to be associated with positive outcomes for workers facing stress Havens et al 2010;Warshawsky, Havens, and Knafl 2012;Havens, Warshawsky, and Vasey 2013;Albertsen et al 2014;Naruse, Sakai, and Nagata 2016).…”
mentioning
confidence: 99%